2019
DOI: 10.1007/s11695-019-04214-7
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in Cirrhotic Patients: Is It Safe?

Abstract: Introduction Ten percent of cirrhotic patients are known to have a high risk of postoperative complications. Ninety percent of bariatric patients suffer from non-alcoholic fatty liver disease (NAFLD), and 50% of them may develop non-alcoholic steatohepatitis (NASH) which can progress to cirrhosis. The aim of this study was to assess whether the presence of cirrhosis at the time of bariatric surgery is associated with an increased rate and severity of short-and long-term cirrhotic complications. Methods A cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
0
28
0
4
Order By: Relevance
“…(109) Nevertheless, for patients with cirrhosis careful consideration must be given in weighing the risks and benefits of bariatric surgery especially as studies have demonstrated that those with cirrhosis may experience significant complications post-surgery. (110,111) Other preventive HCC treatments should include counseling for the cessation of smoking and reducing alcohol consumption, when appropriate, as well as management of hypercholesteremia and type 2 diabetes and obesity, if present. (112,113) In fact, some treatment of risk factors for NASH may provide potential benefit for HCC.…”
Section: Outcome Of Patients With Nafld and Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…(109) Nevertheless, for patients with cirrhosis careful consideration must be given in weighing the risks and benefits of bariatric surgery especially as studies have demonstrated that those with cirrhosis may experience significant complications post-surgery. (110,111) Other preventive HCC treatments should include counseling for the cessation of smoking and reducing alcohol consumption, when appropriate, as well as management of hypercholesteremia and type 2 diabetes and obesity, if present. (112,113) In fact, some treatment of risk factors for NASH may provide potential benefit for HCC.…”
Section: Outcome Of Patients With Nafld and Hccmentioning
confidence: 99%
“… 108 Nevertheless, for patients with cirrhosis, careful consideration must be given to weighing the risks and benefits of bariatric surgery, especially as studies have demonstrated that those with cirrhosis may experience significant complications post-surgery. 109 , 110 …”
Section: Treatmentmentioning
confidence: 99%
“…73,74 Case-control studies have reported a significantly higher postoperative major complication rate (approximately 12%) in patients with cirrhosis, albeit with an acceptably low mortality rate. 73,75 Laparoscopic procedures in the cirrhotic patient warrant precautions such as well-thought-out trocar placement, careful pneumoperitoneum pressurization, patient positioning taking into account oversized liver lobes, and the avoidance of postoperative abdominal drains. 76 Notably, the complication rate following SG was lower than after RYGB (31.3% vs. 14.6% for any complication).…”
Section: Safety In Cirrhosismentioning
confidence: 99%
“…Dies entspricht den Daten aus dem amerikanischen Register (American College of Surgeons National Surgical Quality Improvement Program), welche die Adipositas-Chirurgie bei dialysepflichtigen Patienten als sicher und effektiv beschreiben [15]. Da Adipositas als Risikofaktor für NASH und in der Folge auch für Leberzirrhose gut bekannt ist [16], wurde -wie zu erwartenbei der Mehrheit unserer Patienten intraoperativ eine Leberzirrhose festgestellt. Bei den Patienten mit Leberzirrhose werden beide Verfahren, LSG und LRYGB, in der Literatur als sichere Eingriffe beschrieben [6,17,18]; auch bei uns wurden beide Verfahren angewendet.…”
Section: Postoperatives Management Und Follow-upunclassified